Lithography - Landis, Stefan (Hoboken, NJ : Wiley-ISTE, 2010)
'Lithography is now a complex tool at the heart of a technological process for manufacturing micro and nanocomponents. A multidisciplinary technology, lithography continues to push the limits of optics, chemistry, mechanics, micro and nano-fluids, etc. This book deals with essential technologies and processes, primarily used in industrial manufacturing of microprocessors and other electronic components'--
Includes bibliographical references and index.
Keywords: Microlithography; TECHNOLOGY & ENGINEERING / Material Science